2019
DOI: 10.1021/acssuschemeng.9b02041
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation (HDO) of Biomass Derived Ketones Using Supported Transition Metals in a Continuous Reactor

Abstract: The hydrodeoxygenation (HDO) of 5-nonanonea model compound for more complex biomass-derived moleculesto n-nonane was investigated using a variety of heterogeneous multifunctional metal-impregnated aluminosilicate catalysts in a packed-bed continuous flow reactor system. Under optimized reaction conditions (200 °C, 1.38 MPa H 2 ), >99% conversion and >99% selectivity to n-nonane was achieved within a 30 min residence time over both Ni (7 wt %) and Co (9 wt %) supported on Perlkat 79-3, a high-surface area amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…However, at the base case assumed lifetime of 2 y, impacts of the catalyst cost were minimal. Alternative, low-cost (<$50/kg) HDO catalysts such as those based on Ni or Co have been demonstrated ( 64 ); however, we estimate that the impact of switching to one of these base-metal catalysts is on the order of one cent per gallon of VFA with a lifetime of 2 y. As noted above, future studies will evaluate VFA clean-up strategies to further reduce sulfur and other impurities as well as the use of nonprecious catalysts ( 65 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, at the base case assumed lifetime of 2 y, impacts of the catalyst cost were minimal. Alternative, low-cost (<$50/kg) HDO catalysts such as those based on Ni or Co have been demonstrated ( 64 ); however, we estimate that the impact of switching to one of these base-metal catalysts is on the order of one cent per gallon of VFA with a lifetime of 2 y. As noted above, future studies will evaluate VFA clean-up strategies to further reduce sulfur and other impurities as well as the use of nonprecious catalysts ( 65 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…The C 14 H 30 O 2 (VIII-X) isomers can also undergo the dehydrogenation reaction to form corresponding ketones. Yang et al reported the HDO of 5nonanone using aluminosilicate supported Ni and Co catalysts, and perceived 5-nonanol as the intermediate product 43 . The HDO reaction was proposed to follow via hydrogenation to 5-nonanol, followed by dehydration and hydrogenation reaction.…”
Section: Reaction Mechanism For Hdo Of the C 15 Fuel Precursormentioning
confidence: 99%
“…Yang et al reported the HDO of 5nonanone using aluminosilicate supported Ni and Co catalysts, and perceived 5-nonanol as the intermediate product. 43 The HDO reaction was proposed to follow via hydrogenation to 5nonanol, followed by dehydration and hydrogenation reaction. HDO of 2-hexanone and 3-hexanone was reported to follow via initial hydrogenation to the corresponding alcohols.…”
Section: Reaction Mechanism For Hdo Of the C 15 Fuel Precursormentioning
confidence: 99%
“…A range of HDO substrates, including cellulose, sugars, furan derivatives, biolipids, bio‐oil, and lignin‐derived oxygenates (Table ), offers a range of alkanes of varied branching and carbon numbers; however, the most important question is which of these HDO substrates has the maximum potential to replace current technology of replacing petroleum‐based fuel and lubricants. A simple model compound, such as 5‐nonanoene, was also used as an ideal substrate for screening many metal catalysts on ZSM‐5 and high‐surface‐area support Perlkat 79‐3 (aluminosilicate) …”
Section: Comparison Of Hdo Substratesmentioning
confidence: 99%
“…Therefore, the use of magnetic NPs may be used to enhance the local temperature to activate the catalyst surface under a cold environment. In addition to the interesting roles played by metal–support interfaces consisting of single‐site HDO functions and isolation of C=C and C=O bonds on the metal surface, depending on synergy . In this regard, formic acid, as one of most used biomass‐based hydrogen sources, can be explored for HDO‐based upgrading and oxygen removal processes, of which lignin valorization is used in addition to thermal energy production .…”
Section: Biorefinery Integrationmentioning
confidence: 99%